Convenient synthesis of regioisomerically pure 5- and 6-functionalized xanthene dyes via SNAr reaction and comparison of their reactivity towards click reaction. Issue 15 (10th April 2020) - Mori, Masaya; Fujikawa, Yuuta; Inoue, Hideshi
Abstract: In this study, we present an efficient and general strategy for the individual preparation of both isomers of 5(6)-functionalized xanthene-based fluorophores. Spectroscopic analysis of the acid-base equilibrium of 5(6)-nitro xanthene dyes has shown that they exist predominantly in the colorless spirolactone form in certain aprotic dipolar solvents. In such solvents, regioisomerically selective ipso -substitution of the nitro group by sodium azide occurs at the 6- position but not at the 5- position due to the electron-withdrawing spirolactone moiety at the para -position, relative to the nitro group. This reaction allows the separation of the isomer with the 6-azide group and the intact 5-nitro isomer. The 5-nitro group of the latter was then reduced to an amino group and subsequently converted to an azide group. This strategy enables the preparation of both the 5- and 6-functionalized isomers individually from a mixture of precursors, which is otherwise unachievable. The azide isomers were then compared in reactivity by strain-promoted azide-alkyne cycloaddition (SPAAC) with bicycle[6.1.0]non-4-yene (BCN). Graphical abstract: Image 1 Highlights: The equilibration between the open and spirocyclic forms of DCF and TMR was analyzed in several polar aprotic solvents. Regioisomer-selective ipso -substitution of the nitro group at the 6-position occurs in certain polar aprotic solvents. Each regioisomer of azide DCF was tested for the SPAAC reaction with BCN. The synthetic strategy presented here is efficient and versatile to prepare both regioisomers of 5(6)-functionalized xanthene fluorophores.